THE IMPACT OF CORPORATE SOCIAL RESPONSIBILITY ON CORPORATE REPUTATION: AN EXAMPLE OF A TECHNOLOGY FIRM - ÖZTÜRK, Serkan (Atlas Journal, 2021)
Organizations today cannot be successful by focusing solely on the short-term gains they will achieve. On the other hand, businesses that deal with the problems of the society they are in, protect consumers and are sensitive to the environment gain competitive advantage by standing out from their competitors. The sensitive and responsible behavior of the enterprises make the concept of corporate social responsibility important. Businesses that want to have a good reputation have to adopt the understanding of corporate social responsibility. In this study, it was tried to determine the effects of corporate social responsibility perception on corporate reputation through an example of a technology company. According to the results of the research, the perception of corporate social responsibility differs significantly according to age and income variables. The perception of corporate social responsibility and all its sub-dimensions have a positive and meaningful relationship with corporate reputation. The perception of corporate social responsibility and all its sub-dimensions positively affect the corporate reputation.